Ayurvedic management of non-alcoholic fatty liver disease with obesity and rheumatoid arthritis– A case report - Amit Nakanekar; Rashmi Jaiswal (Phytomedicine Plus)
Background: Non-alcoholic fatty Liver Disease (NAFLD) is one of the leading causes of chronic liver diseases, with a 25 % frequency worldwide. NAFLD is characterized by a complex ''multi-hit'' pathogenesis and spectrum of disorders. In Ayurveda, it is considered under Yakrit vikar (∼liver disease) with Medoroga (∼disease caused by excessive fat deposition). Purpose: A 52-year-old non-alcoholic male patient came with complaints of abdominal distension, fatigue, weakness, back pain, bilateral upper limb tingling, striae present over the thigh and abdomen, bilateral shoulder joint stiffness, anorexia, constipation, and pain at the planter region for the last six months. The patient was admitted to a government medical college and was treated with NSAIDs, Antibiotics, antacids, steroids, and some multivitamin tablets for Grade II fatty liver disease. However, the recurrence occurred, so the patient came to Ayurveda for the same complaints with more added pain in all joints. Study design: The patient was treated using Santarpana (∼overconsumption and sedentary lifestyle) and Krumighn Chikitsa (∼ treatment aimed at eliminating parasites). The specialty of this case is that Krumighna treatment worked well in NAFLD, rheumatoid arthritis, and obesity. The patient was treated for around four months with Basti (∼medicated enema using oil and decoction) and Ayurvedic oral medicines. Result: A remarkable improvement was shown in clinical symptoms, weight, and abdomen and pelvis ultrasound findings. Conclusion: further studies must be conducted to obtain more scientific evidence for the efficacy of this Ayurvedic approach.